2018
DOI: 10.4314/mcd.v13i1.6
|View full text |Cite
|
Sign up to set email alerts
|

The use of natural resources to improve household income, health, and nutrition within the forests of Kianjavato, Madagascar

Abstract: Understanding natural resource extraction in Madagascar is key to developing wider conservation and management strategies that ensure the continued delivery of essential ecosystem services, and the development of health and economic strategies to meet ARTICLE

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 0 publications
1
14
0
1
Order By: Relevance
“…Those surveyed ate 6,726 forest animals (mean of 7 mammals and 10 birds per household), or ∼3.27 kg of wild meat per person (4.48 kg per adult equivalent) during the prior year. This amount of wildlife is much higher than that reported in other regions of Madagascar including Kianjavato (Borgerson et al, 2018a), Alaotra (Borgerson et al, 2018b), and Betampona (Golden et al, 2014b), but it is similar to that reported in nearby Makira (Golden et al, 2014a;Brook et al, 2019), and far less than the amount eaten in the Amazon and Congo basins (63 and 51 kg/capita/year, respectively; Nasi et al, 2011). Further, as much as 75% of all meat eaten in some communities was from forest animals.…”
Section: Discussionsupporting
confidence: 51%
“…Those surveyed ate 6,726 forest animals (mean of 7 mammals and 10 birds per household), or ∼3.27 kg of wild meat per person (4.48 kg per adult equivalent) during the prior year. This amount of wildlife is much higher than that reported in other regions of Madagascar including Kianjavato (Borgerson et al, 2018a), Alaotra (Borgerson et al, 2018b), and Betampona (Golden et al, 2014b), but it is similar to that reported in nearby Makira (Golden et al, 2014a;Brook et al, 2019), and far less than the amount eaten in the Amazon and Congo basins (63 and 51 kg/capita/year, respectively; Nasi et al, 2011). Further, as much as 75% of all meat eaten in some communities was from forest animals.…”
Section: Discussionsupporting
confidence: 51%
“…Additionally, northern populations experience greater intensities of hunting pressures compared to southern populations 108 , which may drive extreme losses in population size and further reduce genetic variability and increase population differentiation through greater levels of inbreeding or local extinctions. Hunting in southern localities has been recently recognized as a threat to populations as well 109 . Further investigations into the local drivers of genetic structure in this taxon are currently underway and will clarify the regional impacts of natural features and landcover modification on more immediate dispersal capacity, as well as more explicitly assess the impacts of historical landcover of observed genetic structure in this taxon.…”
Section: Discussionmentioning
confidence: 99%
“…These wild foods are critically important in increasing dietary diversity, especially given the scarcity and cost of animal-source foods, high-starch diets with low micronutrient content, and the potential for extreme weather events, climate change and disease to disrupt agroecosystems. These challenges are even more important to understand in the context of remote rainforest areas of north-eastern Madagascar where reliance on wild foods is much higher than other parts of the country ( 9 ) and where seasonality will likely play a large role in determining the quantity and quality of foods available. By characterizing the diet in these remote regions, policy makers and public health practitioners can best identify foods that are culturally and nutritionally important, and target interventions to reduce rates of malnutrition of similar populations.…”
mentioning
confidence: 99%